Synergistic effects of combined hypnotic drugs on sleep in mice - Bai, Rui; Wang, Chu; Wu, Fanghui; Yin, Yifeng; Liu, Yanli; Gao, Yuan; Song, Yunyang (Frontiers in Pharmacology, 2025)
Study objectivesTo investigate the interaction and potential mechanisms of the combined administration of dexmedetomidine (DMED) and eszopiclone (ESZ) on sleep in mice.MethodsThe effects of DMED, ESZ and the combination of the two drugs on the sleep status of mice were investigated by using the loss of righting reflex (LORR) as an indicator, the sleep-related parameters were recorded, and the interactions of the combination of DMED and ESZ on sleep were determined by isobolographic analysis. The effects of DMED and ESZ on sleep structure, the regulation of c-Fos protein expression in the ventrolateral preoptic area (VLPO) and the tuberomammillary nucleus (TMN) and the regulation of neurotransmitter levels were further investigated by combining electroencephalogram/electromyogram (EEG/EMG) sleep phase analysis, c-Fos immunofluorescence, and neurotransmitter content measurements in the brain.ResultsIsobolographic analysis demonstrated that the combination of DMED and ESZ had a synergistic effect on sleep in mice. The duration of non-rapid eye movement (NREM) sleep was significantly prolonged; the number of c-Fos positive neurons increased in the VLPO and decreased in the TMN; the levels of excitatory neurotransmitters were reduced, while the levels of inhibitory neurotransmitters were elevated.ConclusionThis study reveals that the combination of DMED and ESZ exerts a synergistic effect on sleep in mice. The underlying mechanism may involve the prolongation of NREM sleep, modulation of neuronal activity in the brain regions of VLPO and TMN, as well as alteration in the levels of brain neurotransmitters.